(untitled) (Applied Biological Research, 2023)
The present epidemiological study was aimed to assess the seasonal prevalence, mean intensity and abundance of gastrointestinal (GI) helminths in goats between January 2017 and December 2019 in Aligarh district of Uttar Pradesh (India). Entire GI tracts from slaughtered goats were brought to the laboratory, dissected and worms from different parts of GI tract were collected, counted and recorded on monthly basis. Eggs per gram of faeces in positive samples were estimated by McMaster technique. The collected data were analysed with respect to rainfall, relative humidity and temperature of months/seasons. Out of 499 goats, 350 were found infected with one or more helminth parasites. Haemonchus contortus was predominant (68.74%), followed by Trichuris ovis 57.72%), Moniezia expansa (23.84%), Oesophagostomum columbianum (15.43%) and amphistomes (9.81%). Considerable variations were noticed in prevalence, mean intensity, abundance and total egg counts during different months/seasons, and the highest values were recorded in monsoon and lowest in winter. Female goats were more infected by all helminth parasites than males. The study provides important information about the seasonal dynamics of helminth parasites, which can be utilized to develop integrated control measures for these parasites in North India.